Decision Support System for Providing Business Capital In Pidie District Using the Web-Based TOPSIS Method - Nurfebruary, Nanda Sitti; Nisa, Fidyatun; Fuadi, Fuadi; Multazam, Teuku; Nasution, Fakhruddin Ahmad (Geuthèë Institute, 2023)
Providing business capital assistance is a poverty alleviation program for people who have medium and small businesses. The Office of Industry and Trade (DISPERINDAGKOP) of Pidie Regency has one of the work programs, namely providing material and equipment assistance to small and medium industries in Pidie Regency. In order to be more efficient and effective in the process of determining whether or not someone is eligible to receive venture capital assistance, a Decision Support System (SPK) was created for the eligibility of recipients of venture capital assistance in Pidie District using the Technique For Others Preference by Similarity to Ideal Solution (TOPSIS) method. The criteria used as an assessment in determining the eligibility of recipients of business capital assistance are underprivileged conditions, economic conditions, conditions of family dependents, housing conditions, condition of type of business. These criteria are obtained based on the table of the amount of venture capital assistance that has been determined by the Pidie District Government. This system is expected to assist DISPERINDAGKOP in providing business capital assistance to the community according to the resulting criteria. Also to overcome the possibility of data duplication and errors in determining the recipient of venture capital.